Strategi Branding dan Pembentukan Kesadaran Merek melalui Konten Visual Media Sosial Instagram - Ari Ramadzan; Dody Iskandar (UNISBA Press, 2024)
Abstract. Nowadays, the easily accessible nature of the internet is able to reach unlimited audiences. That is why business actors such as coffee shops are starting to use social media to spread information and create awareness of their products or services. One of them is a coffee shop in Bandung City, Cap Dangu. Utilizing visual media content on features on Instagram creates very good impressions and enthusiasm from coffee business people or coffee connoisseurs. Especially at the